Diagnóstico ambiental participativo: estudo de caso na comunidade indígena Xucuru-Kariri em Caldas/MG - Nogueira, Ana Caroline Costa (2015)
Predatory process of urbanization has caused many traditional communities lose their spaces and their traditions they are forced to adapt to a new reality. Involving people to diagnose the reality and make them participate in the actions change, can possibly be a solution for future projects in the quest for preservation of natural resources. Conduct an environmental review through a participatory diagnosis aiming the perception of the community in an attempt to seek environmental enhancement, enabling the incorporation of preserving environment and encourage sustainable living, it was the aim of this study. With this took place the study in Indian village Xucuru - Kariri in the municipality of Caldas / MG, to identify local environmental impacts. With the actions of Environmental Participatory Diagnosis, made ​​possible via visits the property and informal conversations, we obtained the environmental aspects and the main local problems, related by themselves diagnosed together to mediators. With the use of participatory methodology we were able to obtain the environmental conditions of the village, in particular the conditions of the springs, the quality of water consumed, as well as local conditions. Through fourteen techniques chosen and adapted to the reality of the community, it was found that the premises of the village there are many idle areas. Which could be better utilized or even reforested. Also there was unprotected springs and relevant issues as health conditions. The community despite being characterized as traditional are living in a property with rural characteristics and urban habits. Problems with the disposal of solid waste is common, are sighted through the houses arranged in their backyards. The area boasts crops intended for subsistence of indigenous and local are still inadequate and located near water courses. Finally, the conclusions are presented on the application and the viability of participatory methodology, which were satisfactory where possible to evaluate the area and identify their environmental impacts with the help of the residents. Note also the efficiency and ease of application in the diagnosis and clarity results.